ANALISIS PERLAKUAN AKUNTANSI TANAMAN PRODUKTIF BERDASARKAN PSAK 16 PADA CV. BUDI BAKTI AGRO - Hamdani Arifulsyah Rangkuti; Fany Meilani; Suci Nurulita (Universitas Pamulang, 2020)
The purpose of this study was to determine how the application of PSAK 16 on productive plants in CV. Budi Bakti Agro was founded in 2000, which is a company engaged in the oil palm plantation sector. CV Budi Bakti Agro has 3 locations of oil palm plantations, namely in Padang Mahondang Village, Sukaramai Village, Batu Anam Village in North Sumatra. CV Budi Bakti Agro in presenting the value of its oil palms in the statement of financial position is at the historucal price and not based on the fair value of the asset. The company presents the statement of financial position as plant fixed assets and there is no separation between mature and immature plantations. This causes the financial statements presented are not relevant in accordance with the qualitative characteristics of the financial statements. After adjusting to the application of PSAK 16, it was determined that the value of the plants produced was Rp. 679,201,740 whose value is the fair value as of December 31, 2016 and the immature plantations amounting to Rp.15,761,010,500 whose value is the fair value as of December 31, 2016.